THE INFLUENCE OF PREVIEW, ASK QUESTIONS, READ, SUMMARIZE (P-A-R-S) STRATEGY AND STUDENTS’ READING ATTITUDE ON COMPREHENDING RECOUNT TEXTS OF THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 29 OF PALEMBANG - Yudi Hariyanto (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACTThe writer was interested in conducting this research in accordance that the students still found difficulties in comprehending recount text. It looked from the result in answering recount text, the students were not achieve the minimum criteria of achievement of English subject of Junior High School 29 of Palembang. This research was conducted in experimental research to 72 students of the eighth grade students of Junior High School 29 of Palembang in the first semester of the academic year of 2013-2014. The objectives of research were to find out whether or not (1) There was a significant difference in average score of comprehending recount texts between the students who are taught using Preview, Ask Question, Read, Summarize (PARS) strategy and those who are taught using conventional strategy; (2) There was a significant difference in average score of comprehending recount texts between the students who are in positive and negative attitude after being taught using Preview, Ask Question, Read, Summarize (PARS) strategy and those who are after being taught using conventional strategy; and (3) There was a significant interaction effect of Preview, Ask Question, Read, Summarize (PARS) strategy and the students’ reading attitude on comprehending recount texts. There were some instruments to achieve the objectives of research: test and questionnaire. Keywords: Preview, Ask Question, Read, Summarize (PARS) strategy, Reading Atitude, and Recount Text